2014
DOI: 10.1155/2014/496705
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Cinobufagin on L-Type Ca2+Currents, Contractility, and Ca2+Homeostasis of Isol

Abstract: Cinobufagin (CBG), a major bioactive ingredient of the bufanolide steroid compounds of Chan Su, has been widely used to treat coronary heart disease. At present, the effect of CBG on the L-type Ca2+ current (I Ca-L) of ventricular myocytes remains undefined. The aim of the present study was to characterize the effect of CBG on intracellular Ca2+ ([Ca2+]i) handling and cell contractility in rat ventricular myocytes. CBG was investigated by determining its influence on I Ca-L, Ca2+ transient, and contractility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…Cinobufagin, which was approved by the Chinese State Food and Drug Administration as a chemotherapeutic drug for liver and prostate cancer treatment in China, is a major active ingredient isolated from the Traditional Chinese Medicine Venenum Bufonis [36]. Although cytotoxic side effects in cardiac myocytes by the administration of a high dose of cinobufagin contained in Chinese Medicine has been reported [37], emerging evidence has shown that cinobufagin effectively suppresses cancer growth and progression by inducing cell cycle arrest and apoptosis and inhibiting angiogenesis [38]. For example, cinobufagin was found to promote cell cycle arrest at the G2/M phase and apoptosis in hepatocellular carcinoma and esophageal squamous cell carcinoma by increasing the expression levels of pro-apoptotic p73 and BAX [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Cinobufagin, which was approved by the Chinese State Food and Drug Administration as a chemotherapeutic drug for liver and prostate cancer treatment in China, is a major active ingredient isolated from the Traditional Chinese Medicine Venenum Bufonis [36]. Although cytotoxic side effects in cardiac myocytes by the administration of a high dose of cinobufagin contained in Chinese Medicine has been reported [37], emerging evidence has shown that cinobufagin effectively suppresses cancer growth and progression by inducing cell cycle arrest and apoptosis and inhibiting angiogenesis [38]. For example, cinobufagin was found to promote cell cycle arrest at the G2/M phase and apoptosis in hepatocellular carcinoma and esophageal squamous cell carcinoma by increasing the expression levels of pro-apoptotic p73 and BAX [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Chan Su, prepared from the auricular glands and skin glands of Chinese toads, is a traditional Chinese medicine which is used in diverse biological conditions such as inflammation, anesthesia and arrhythmia . As a traditional Chinese medicine, Chan Su has been listed in Pharmacopoeia of People's Republic of China (State Pharmacopoeia Committee, 2010) . The extracts of Chan Su play an important role in cardiac disease; they are described as dried toad venom in English, ‘toad cake’ in China, ‘Senso’ in Japan and ‘Somsa’ in Korea .…”
Section: Introductionmentioning
confidence: 99%
“…Bufalin (C 24 H 34 O 4 ) is one of the main active components of Chan Su . We recently showed that cinobufagin (another active ingredient in Chan Su) inhibits the L‐type calcium channels (LTCCs) .…”
Section: Introductionmentioning
confidence: 99%
“…Calcium current is the primary inward current in cellular membrane repolarization, and Ca 2+ cycling regulates cardiac contraction. Increased [Ca 2+ ] I is also a critical sign of cell apoptosis, and has been associated with a number of abnormalities in cardiac tissues, such as ventricular arrhythmias and contractile dysfunction [ 8 ]. ATO can augment I Ca, L density, triggering intracellular calcium overload and disorder, and ultimately inducing arrhythmia and cell apoptosis [ 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%